A COGNITIVE METAPHOR ANALYSIS OF DONALD TRUMP'S SPEECHES - Lingga, Thomson Radesman; Sirait, Debora Serwanti; Sirait, Asnita (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Metaphorical expressions carry layered meanings and serve a range of persuasive functions, especially within the political sphere. Their strategic use often aims to influence public perception and reinforce a speaker’s credibility. Donald Trump’s presidential campaign speeches during the 2016–2017 U.S. election cycle offer a compelling corpus for examining such rhetorical choices. This study analyzes the metaphors in these speeches by categorizing them into three types: structural, ontological, and orientational metaphors. Using a qualitative descriptive design grounded in cognitive metaphor theory, the analysis draws on Lakoff and Johnson’s Metaphors We Live By (1980). Operating within a post-positivist paradigm, the researcher serves as the primary instrument in interpreting the data. The findings show that structural metaphors allow Trump to frame abstract ideas through more concrete conceptual structures; ontological metaphors provide moderate conceptual grounding by attributing entity-like qualities to abstract phenomena; and orientational metaphors offer minimal conceptual structure while shaping spatial or directional understandings. Across these categories, Trump’s metaphors function to evoke emotion, shape audience perception, and construct a particular persona. Taken together, the metaphors project a worldview centered on resilience, national pride, and assertive leadership—features that contributed to the persuasive force of his political messaging.